2022
DOI: 10.3390/app12146830
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study of Pressure Drop Characteristics of Soybean Grain under Vertical Pressure

Abstract: The vertical pressure lead to increased airflow resistance through the grain bulk, which affected the efficiency of ventilation and drying. The effects of vertical pressures at 50, 150, and 250 kPa on the pressure drop characteristics of soybeans were studied using experiment and numerical simulation. The random packing and different compression states for soybean packed beds were generated by the Discrete Element Method (DEM). The Discrete Element Method (DEM) and Computational Fluid Dynamics (CFD) were coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…Figure 6 shows the comparison of the OpenFOAM simulations using the Darcy-Forchheimer model with experimental data from Khatchatourian & Savicki (2004). The experimental data showed that the relationship between airflow velocity and airflow pressure drop depends on the grain layer height (H); it happens because of the compaction in the lower regions, which decreases the porosity, as evidenced by Liu et al (2022) and Nwaizu & Zhang (2021). The prediction from the OpenFOAM software using Darcy-Forchheimer model shows good agreement with the experimental data.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Figure 6 shows the comparison of the OpenFOAM simulations using the Darcy-Forchheimer model with experimental data from Khatchatourian & Savicki (2004). The experimental data showed that the relationship between airflow velocity and airflow pressure drop depends on the grain layer height (H); it happens because of the compaction in the lower regions, which decreases the porosity, as evidenced by Liu et al (2022) and Nwaizu & Zhang (2021). The prediction from the OpenFOAM software using Darcy-Forchheimer model shows good agreement with the experimental data.…”
Section: Resultsmentioning
confidence: 73%
“…Both parameters have a nonlinear dynamic, and both curve-fitting procedures obtained a R² above 0.95. Liu et al (2022) used a different method to estimate the parameters D and F, based on Discrete Element Method (DEM), and obtained D in the range from 17740438 to 47576815, and F in the range from 382 to 659. These parameters were not obtained as function of grain layer height, therefore, a direct comparison cannot be possible; but there is an intersection for the parameter D in both studies, whereas the range of the parameter F in Liu et al ( 2022) is smaller and outside the range of these results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effect of pore structure on the temperature field remains neglected. Few researchers have constructed pore structures and analyzed the airflow distribution within the grain pile using the DEM packing model (Liu, Dhamankar, et al, 2022; Liu et al, 2022). To simplify CFD pretreatment models, in studies of near‐spherical food products such as apples (Delele et al, 2008; Han et al, 2017) and pomegranates (Ambaw et al, 2017), scholars have mainly used spheres instead of real food shapes to obtain data on local airflow distribution and temperature variation.…”
Section: Introductionmentioning
confidence: 99%
“…They accomplished this by modifying the granary structure, inlet duct configurations, inlet velocity conditions, and grain packing forms (Alagusundaram et al, 1990; Kashaninejad et al, 2010; Khatchatourian & De Oliveira, 2006; Nawi et al, 2010; Zhang, Xia, et al, 2022; Zhang, Zhang, et al, 2022). Although the particle‐resolved computational fluid dynamics (PRCFD) method, which restores the packing structure and porosity distribution of particles in a fixed bed, and solves the heat and mass transfer inside particles, was available, its high computational cost made it unsuitable for large‐scale practical production (Ambaw et al, 2017; Liu et al, 2022). Consequently, developing an improved homogeneous continuous numerical models with appropriate computational efficiency and accuracy is essential to investigate the actual flow and heat transfer processes in grain piles.…”
Section: Introductionmentioning
confidence: 99%